Prosocial CEOs, corporate policies, and firm value - FENG, Mei (Institutional Knowledge at Singapore Management University, 2024)
This paper examines how chief executive officers' (CEOs') prosocial tendency influences corporate policies and firm value. We use individuals' involvement with charitable organizations as a proxy for prosocial tendency. We find that, compared to firms with non-prosocial CEOs, firms with prosocial CEOs have lower executive subordinate turnover, implement more employee-friendly policies, experience higher customer satisfaction, and engage in more socially responsible activities. We also find that firms with prosocial CEOs have higher value and lower risk, partly due to the corporate policies adopted by prosocial CEOs. These results are corroborated when we compare changes in corporate policies and firm value around different types of CEO turnovers: a prosocial CEO replacing a non-prosocial CEO versus other types. Our results thus suggest that prosocial CEOs are more likely to make corporate decisions that benefit others and increase firm value.